Comparison of Triage Duration Using the Early Warning Score (EWS) and the Emergency Severity Index (ESI) by Nursing Student - Vita Maryah ardiyani; Wahyu Dini Metrikayanto; Ani Sutriningsih; Putu Sintya Arlinda; Risna Yekti Mumpuni; Yati Srihayati; Indah Dwi Pratiwi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2026)
Background: Triage is a crucial competency for nurses in the field of emergency nursing, as it determines the level of urgency for each patient. The concept of emergency care focuses on the triage system, which classifies patients based on the severity of their condition. Although triage methods vary across countries, the fundamental principle remains the same: prioritizing patients according to the severity of their condition and the resources available. Two triage methods that can be applied based on patients’ clinical signs and are in line with nursing competencies are the Emergency Severity Index (ESI) and the Early Warning Score (EWS). Nursing students, as novice healthcare providers preparing for clinical practice, must be equipped with a strong understanding of triage. It is therefore essential to introduce various triage methods to students, particularly through the application of these methods in clinical case simulations, which they are likely to encounter during clinical practice. This underpins the urgency of research comparing triage time between the ESI and EWS methods. The objective of this study was to analyze nursing students’ ability to apply triage using ESI and EWS, and to compare triage duration between these two methods in simulated clinical cases (vignette-based scenarios). Methods: The study employed an experimental design with a one-group pretest–posttest approach, where clinical case vignettes were presented to be assessed using both ESI and EWS methods. Results: The respondents consisted of 200 undergraduate nursing students drawn from five nursing education institutions in Malang City and Regency. Mann–Whitney test results indicated a significance value of 0.000, demonstrating a significant difference in triage duration between the ESI and EWS methods. Conclusions: The findings revealed that the ESI method was faster than the EWS method. All respondents were undergraduate nursing students with limited clinical experience. Future studies are recommended to examine the implementation of ESI and EWS methods in emergency departments or critical care units in hospital settings